Audit Quality of The Engagement Partner and Audit Firm - Elfina Astrella Sambuaga; Antonius Herusetya (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study examines the effect of the number of clients and complexity on audit quality at the audit engagement partner (AEP) and public accounting firm (PAF) levels. We use discretionary accrual and real activities manipulation models to assess the audit quality at the AEP and PAF levels. Our study examines 506 firm-year observations as our sample for the companies in the industrial sector listed on the Indonesian Stock Exchange. Using multiple linear regressions and controlling for year and industry fixed effects, our study discovered that the client complexity handled by AEPs is associated with the declining audit quality of AEPs using discretionary accruals. However, our study discovered no relationship between the number of clients at the AEP and PAF levels, and client complexity at the PAF level that influences the audit quality. Thus, the findings of our study suggest to standard setters, capital market participants, and other stakeholders that audit quality at the AEP level remains a significant concern.